(3MGTjI Ydi TQM GdNWjH GdTQHjfj Ydi TQM ZGjI GdGNJUGQs - (3GdLed, SdjeGf Hf YeQ Hf efUhQ, J (B1204 (3g`s ((3YHO GdeMSf GdHQHQGhjs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf HSe Gddg GdN SjCJj GdcdGe Ydi eG jJYdb HGdHSedI hGdMeOdI bhdg GdMeO ddg EdN GTJed cdGeg ef gfG Edi hHYO Ydi GKfJj YTQI SLYIs
(3BNQgG (B:s
(3bhdg Yfj Cj Ydi LhGH GdTQW eMPha Cj agh GdeWdhH hjchf bhdg adG RGd EdN EeG eSJCfa Ch Gfg Ydi eYfi hdh RGd ZVHGfG hjchf ZGjI aj GdLhGH GdebOQ bhdg ZVHGfG CUdg ZVHGfjf hCaQOg ddhRfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 131s
(3eYLe GdeDdajf (B1 / 795s
(3gOjI GdYGQajf (B1 / 406s
(3MdjI GdHTQ (B2 / 62s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs